Shadow economy over the business cycle: how do formal and informal cycles interact? - Birinci, Serdar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
In this thesis, first, relying on a two-sector dynamic general equilibrium model, I construct quarterly estimates of shadow economy size for 15 advanced economies for a time period from 1960 to 2010. This gives me the largest quarterly shadow economy size data in the literature. Next, using this novel data, I provide a comprehensive empirical characterization of the linkages between the formal and the shadow economies around the business cycles. The results indicate that the shadow economy size as a percentage of official GDP is generally countercyclical and a larger shadow economy is associated with a larger amplitude and longer duration of formal expansions and larger amplitude of formal recessions.
Keywords: Informal sector (Economics); Business cycles.